2019
DOI: 10.1080/10715762.2019.1635252
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene reverses palmitic acid mediated insulin resistance in HepG2 cells by reducing oxidative stress and triglyceride accumulation

Abstract: Insulin resistance (IR) is known to precede onset of type 2 diabetes and increased oxidative stress appears to be a deleterious factor leading to IR. In this study, we evaluated ability of Pterostilbene (PTS), a methoxylated analog of Resveratrol and a known antioxidant, to reverse palmitic acid (PA)-mediated IR in HepG2 cells. PTS prevented ROS formation and subsequent oxidative lipid damage by reducing the expression of NADPH Oxidase 3 (NOX3) in PA treated HepG2 cells. Hepatic glucose production was used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…Liver is a critical metabolic organ in maintenance of glucose and lipid homeostasis (Birkenfeld & Shulman, 2014). It has been shown that excessive nutrients induce a greater increase in liver fat and insulin resistance and long-term treatment with PA can cause IR (Malik et al, 2019). PA-induced cells have been widely used as an IR model in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Liver is a critical metabolic organ in maintenance of glucose and lipid homeostasis (Birkenfeld & Shulman, 2014). It has been shown that excessive nutrients induce a greater increase in liver fat and insulin resistance and long-term treatment with PA can cause IR (Malik et al, 2019). PA-induced cells have been widely used as an IR model in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the NADPH oxidase (NOX) is critical to the production of ROS in the organism. Previous studies showed that the ROS production increased by up-regulating the expression of NADPH oxidase 3 (NOX3), activating p38MAPK and JNK signaling pathway, and inducing insulin resistance in palmitate-induced HepG2 cells (Gao et al, 2010;Malik et al, 2019). Our studies found that skimmin can inhibit palmitic acid-induced the production of ROS, and 40 mmol/L skimmin was more obvious using flow cytometry assay (P < 0.05), which was better than metformin, a drug used to treat diabetes ( Figure 3A).…”
Section: Skimmin Increase the Uptake Of Glucose By Reducing The Activmentioning
confidence: 99%
“…HepG2 cells are currently widely applied to study fatty liver (Chen et al, 2018). Palmitic acid (PA) is one of the most common saturated fats in the diet (Malik et al, 2019). The culture medium containing PA can induce the HepG2 cells to produce IR and can also better simulate the nutritional obesity status of the human liver (Mo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%